1991
DOI: 10.1088/0031-9155/36/9/002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anode and filter material on image quality and glandular dose for screen-film mammography

Abstract: The influence of anode and filter materials on the performance (image quality and dose) of a mammography system is investigated. The image quality is evaluated with the image quality index method. A computer simulation has been developed to calculate the physical parameters of the image quality index (contrast, resolution and noise) as well as the mean glandular dose. The calculations take into account the successive steps of the process: x-ray production, filtration, interaction with the test object, anti-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…In film/screen mammography, the molybdenum/molybdenum (Mo/Mo) anode/filter combination has traditionally been the most commonly used, but other choices have also been introduced, especially for imaging thick breasts [4][5][6][7]. Selected beam qualities have been studied for their suitability for use in digital mammography [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In film/screen mammography, the molybdenum/molybdenum (Mo/Mo) anode/filter combination has traditionally been the most commonly used, but other choices have also been introduced, especially for imaging thick breasts [4][5][6][7]. Selected beam qualities have been studied for their suitability for use in digital mammography [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…23 The detectability of µCa could potentially be improved if spectral information is optimally utilized in future studies, although the CNR improvement from energy weighting will depend on the detector efficiency and input spectra. 3,23…”
Section: Mgdmentioning
confidence: 99%
“…1 Early and reliable detection of breast cancer can potentially reduce the mortality rate. 2 So far, various x-ray imaging techniques have been investigated for the early detection of breast cancer including two-dimensional (2D) mammography, [3][4][5][6] which is the most common imaging technique for screening, and threedimensional (3D) methods, such as digital breast tomosynthesis 7,8 and dedicated breast cone beam computed tomography (CBCT). [9][10][11] Digital breast tomosynthesis and CBCT have been developed to solve the problem caused by overlapping anatomical structures in 2D mammography.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that optimization in digital mammography usually depended on how can maximized the figure of merit (FOM). Desponds et al investigated the image quality index with respect to the anode-filter combination without dose penalty and concluded that the use of a W anode with a Rh filter was the best choice of anode-filter combination for dose reduction without degradation of image quality [14]. Ullman et al demonstrated the optimal X-ray tube voltage and anode-filter combination in digital iodine contrast media mammography to maximize the FOM by using Monte Carlo simulations [8].…”
Section: Simulation Set-upmentioning
confidence: 99%